2020
DOI: 10.1002/anie.201914026
|View full text |Cite
|
Sign up to set email alerts
|

Optical Waveguiding Organic Single Crystals Exhibiting Physical and Chemical Bending Features

Abstract: Bendable (elastic and plastic) organic single crystals have been widely studied as emerging flexible materials with highly ordered packing structures. However, even though manifold bendable organic crystals have been recently reported, most of them bend in response to only one stimulus. Herein, we report an organic single crystal of (Z)‐4‐(1‐cyano‐2‐(4‐(dimethylamino)phenyl)vinyl)benzonitrile, which bends under external stress (physical process) and also hydrochloric acid atmosphere (chemical process). This ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 44 publications
0
66
1
1
Order By: Relevance
“…10 In 2012, Reddy and coworkers reported a kind of organic co-crystal that exhibited elastic bending ability under applied stress. 11 Subsequently, elastic and plastic organic crystals have been rapidly developed and deeply studied by Desiraju 12,13 , Naumov [14][15][16] , Reddy 17.18 , Hayashi 19,20 , Chandrasekar 21, 22 and our group [23][24][25][26][27][28] Notably, flexible organic crystals compatible with optical and electrical functions have been reported recently, which advanced the application of these flexible materials in optoelectronics. [29][30][31] There are two key limiting factors in expanding the application of flexible organic crystals: single mechanical property and narrow applicable temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2012, Reddy and coworkers reported a kind of organic co-crystal that exhibited elastic bending ability under applied stress. 11 Subsequently, elastic and plastic organic crystals have been rapidly developed and deeply studied by Desiraju 12,13 , Naumov [14][15][16] , Reddy 17.18 , Hayashi 19,20 , Chandrasekar 21, 22 and our group [23][24][25][26][27][28] Notably, flexible organic crystals compatible with optical and electrical functions have been reported recently, which advanced the application of these flexible materials in optoelectronics. [29][30][31] There are two key limiting factors in expanding the application of flexible organic crystals: single mechanical property and narrow applicable temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Zhang and co-workers reported the physical (external stress) and chemical (vapor exposure) mediated bending in (Z)-4-(1-cyano-2-(4-(dimethylamino)phenyl)vinyl) benzonitrile (CN-DPVB) crystals (Figure 11A-D). [27] The crystal bending was achieved by applying external stress multiple times. However, when the stress was removed from the crystal, it attains its original shape; revealing its elasticity ( Figure 11E The crystal was exposed to acidic atmosphere using different volatile acids namely formic acid, acetic acid, propionic acid, trifluoroacetic acid, and hydrochloric acid (HCl); among them, only HCl caused bending of the crystal ( Figure 11F).…”
Section: Flexible Single-crystal Organic Optical Waveguidesmentioning
confidence: 99%
“…Reproduced with permission. [27] Copyright 2020, Wiley-VCH. www.advopticalmat.de line) formed a π-π stacked molecular chain along the crystallographic a-axis.…”
Section: Flexible Single-crystal Organic Optical Waveguidesmentioning
confidence: 99%
“…[18] Recently, organic crystals with elasticity or plasticity have been emerging as a cutting-edge research field in crystal engineering. [19][20][21][22][23][24][25][26][27][28][29][30][31] Desiraju and co-workers found that the anisotropic packing structure contributed to the plasticity of 2-(methylthio)nicotinic acid crystals. [32] Reddy and co-workers reported the elastic bendable organic cocrystal and provided insights into the mechanism of crystal elasticity.…”
mentioning
confidence: 99%